Framing financial advertising: message effectiveness in intertemporal choice. Issue 3 (2nd April 2020) - Kim, Kenneth; McKinnon, Lori Melton
Abstract: The current study examined the effectiveness of retirement financial services advertising (RFSA) in consumer intertemporal choice. When consumers make decisions on retirement savings, they face trade-offs: when should they start saving, how much do they need to invest, and how much do they need to retire? Specifically, this study explored the effectiveness of a financial services advertisement stressing the investment process for retirement savings (that is, process framing) and a financial services advertisement emphasizing the outcome of investment (that is, outcome framing) in combination with gain and loss frames. The obtained data indicated that people in the process framing condition had a stronger tendency to choose the earlier saving option over the delay option when an ad was presented in terms of losses versus gains. In contrast, the advantage of gains (vs. losses) was found in the outcome framing condition. Some implications for strategic advertising messages to promote early retirement savings were discussed.